Towards site-specific greenhouse gas emissions measurement: Rice production in Colombia - Andrade, R.; Esponda, M.; Ibarra, L.; Romero Sánchez, Miguel Antonio (2023)
This study contributes to the lack of national information on rice emissions. Impact mitigation should focus on reducing methane emissions through different strategies. Estimation can be complemented with a deeper study of other activity sources such as fuel use, land preparation between crop seasons, harvesting, etc. Consider having a representative sample not only in production but also in the different practices of rice cultivation.